Porous carbon-sodium ferric phosphate pyrophosphate composite material as well as preparation method and application thereof

By using porous carbon-sodium phosphate sodium pyrophosphate composite material in sodium ion capacitors, the problem of low specific capacity and energy density of the positive electrode material of sodium ion capacitors is solved, the conductivity and sodium ion transfer speed are improved, and the overall device is improved performance.

CN119324124APending Publication Date: 2025-01-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310867583.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The specific capacity and energy density of the existing sodium ion capacitor positive electrode materials are low, and the electron conductivity of sodium ferric pyrophosphate and slow sodium ion transport limit the performance of the device.

Method used

Porous carbon-sodium phosphate sodium pyrophosphate composite material is used as the positive electrode material of sodium ion battery. By distributing sodium phosphate phosphate in the surface and pores of porous carbon, the high specific surface area and conductivity of porous carbon are used to combine iron pyrophosphate. The high specific capacity of sodium increases the energy density and conductivity of sodium ion capacitors.

Benefits of technology

The specific capacity of the positive electrode of the sodium ion capacitor is significantly improved, the electronic conductivity of sodium ferric pyrophosphate and sodium ion transfer speed are improved, the energy density and power density of the device are improved, and the safety risk of resistance heating is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324124A_ABST
    Figure CN119324124A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon-sodium ferric phosphate pyrophosphate composite material and a preparation method and application thereof, the composite material comprises porous carbon and sodium ferric phosphate pyrophosphate, and the sodium ferric phosphate pyrophosphate is distributed on the outer surface of the porous carbon and in porous carbon channels. The preparation method of the porous carbon-sodium ferric phosphate pyrophosphate composite material comprises the following steps: (1) preparing a sodium ferric phosphate pyrophosphate precursor solution; (2) uniformly mixing the ferric sodium pyrophosphate precursor solution obtained in the step (1) with porous carbon to obtain a precursor material flow; and (3) drying and roasting the precursor material flow obtained in the step (2) to obtain the porous carbon-phosphoric acid ferric sodium pyrophosphate composite material. According to the method, the composite electrode material with high rate performance can be obtained, and the energy density can be greatly improved when the composite electrode material is applied to a sodium ion capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy, and in particular relates to a positive electrode material for a sodium ion capacitor and a preparation method thereof. Background Art

[0002] Under the dual carbon goals, the proportion of renewable energy represented by wind and solar energy is increasing, but intermittent renewable energy needs to be coupled with energy storage systems to be connected to the grid. In recent years, electrochemical energy storage technology has developed rapidly. Among them, supercapacitors have the advantages of high charging and discharging power, long cycle life, and a wide operating temperature range. They can be used to smooth out grid fluctuations caused by renewable energy. However, the energy density of traditional double-layer supercapacitors is not high and the application cost is relatively high. If relatively cheap and resource-rich sodium-ion batteries are combined with double-layer capacitors to form sodium-ion capacitors, it is expected that the energy density of the device can be greatly improved.

[0003] The positive electrode of the sodium ion capacitor uses the porous carbon material of the double-layer capacitor, relying on the high specific surface area to adsorb ions for energy storage. The negative electrode uses the amorphous carbon material of the sodium ion battery, relying on the embedding and release of sodium ions inside the negative electrode for energy storage. The specific capacity of the porous carbon positive electrode material is the main factor determining the energy density of the sodium ion capacitor.

[0004] At present, the reversible specific capacity of porous carbon positive electrodes is generally 30 to 70 mAh / g, which is mainly limited by the specific surface area of ​​the material. In addition, the high porosity problem caused by the high specific surface area is not conducive to the energy density and conductivity of sodium ion capacitors.

[0005] CN114975973A relates to a modified high-performance sodium iron pyrophosphate sodium ion battery positive electrode material, its preparation and application, and adopts a solid phase method to prepare the modified high-performance sodium iron pyrophosphate sodium ion battery positive electrode material, which first forms a carbon coating layer on the surface of Na2FeP2O7, and then mixes and sinters with carbon nanotubes, so that the carbon coating layer is connected with the carbon nanotubes to form a conductive network, and the modified high-performance sodium iron pyrophosphate sodium ion battery positive electrode material is obtained. It is to coat the surface of sodium iron pyrophosphate with carbon, which cannot achieve the effect of reducing the particle size, and the pore structure of the coated carbon is underdeveloped, the specific surface area is low, and it cannot provide capacity by itself, which will reduce the energy density of the device. Summary of the invention

[0006] In view of the need for high specific capacity sodium ion capacitor positive electrode materials, the main purpose of the present invention is to provide a porous carbon-sodium iron phosphate pyrophosphate composite material and its preparation method and application. When the porous carbon-sodium iron phosphate pyrophosphate composite material is used as a sodium ion battery positive electrode material, it can increase the specific capacity of the sodium ion capacitor positive electrode by more than 20%, and at the same time, it can also increase the energy density of the sodium ion capacitor; it solves the problems of poor electronic conductivity of sodium iron phosphate pyrophosphate and slow sodium ion transmission.

[0007] A first aspect of the present invention provides a porous carbon-sodium iron phosphate pyrophosphate composite material, the composite material comprising porous carbon and sodium iron phosphate pyrophosphate, wherein the sodium iron phosphate pyrophosphate is distributed on the outer surface of the porous carbon and in the pores of the porous carbon.

[0008] Furthermore, in the porous carbon-sodium iron phosphate pyrophosphate composite material, the porous carbon content is 10wt% to 90wt%, preferably 25wt% to 80wt%, based on the total weight of the composite material.

[0009] Furthermore, in the porous carbon-sodium iron phosphate pyrophosphate composite material, the specific surface area of ​​the porous carbon-sodium iron phosphate pyrophosphate composite material is 1000 to 3600 m 2 / g, preferably 2500 to 3400m 2 / g.

[0010] Furthermore, in the above-mentioned porous carbon-sodium iron phosphate pyrophosphate composite material, the pore size distribution of the composite material has the following characteristics: the pore volume occupied by its mesopores is 5% to 50% of the total pore volume of micropores and mesopores, and more preferably 10% to 30%; wherein the pore size of the mesopores is 2 to 50 nm, and the pore size of the micropores is less than 2 nm.

[0011] Furthermore, in the above-mentioned porous carbon-sodium iron pyrophosphate composite material, the porous carbon can come from one or more of biomass such as coconut shells, corn cobs, and wood; or from one or more of petroleum-based raw materials such as petroleum coke and petroleum asphalt; or from one or more of other raw materials such as starch, coal, and coal tar.

[0012] Furthermore, in the porous carbon-sodium iron phosphate pyrophosphate composite material, the porous carbon is in powder form, and the particle size of the porous carbon is generally 1 to 100 μm, preferably 3 to 20 μm. The pore size distribution of the porous carbon has the following characteristics: the pore volume occupied by the mesopores is 20% to 50% of the total pore volume of the micropores and mesopores, and more preferably 30% to 40%; wherein the pore size of the mesopores is 2 to 50 nm, and the pore size of the micropores is less than 2 nm. The specific surface area of ​​the porous carbon is 500 to 3500 m 2 / g, preferably 1000 to 3000 m 2 / g.

[0013] Furthermore, in the porous carbon-sodium iron phosphate pyrophosphate composite material, the characteristic diffraction peak of sodium iron phosphate pyrophosphate measured by X-ray diffraction method, and its statistical crystal size calculated by Scherrer formula is 2 to 50 nm, preferably 5 to 20 nm.

[0014] The second aspect of the present invention provides a method for preparing a porous carbon-sodium iron phosphate pyrophosphate composite material, and the preparation method comprises the following steps:

[0015] (1) preparing a sodium iron phosphate pyrophosphate precursor solution;

[0016] (2) mixing the sodium iron phosphate pyrophosphate precursor solution obtained in step (1) with porous carbon to obtain a precursor stream after mixing;

[0017] (3) The precursor material obtained in step (2) is dried and calcined to obtain a porous carbon-sodium iron phosphate pyrophosphate composite material.

[0018] Furthermore, in the preparation method of the porous carbon-sodium iron phosphate pyrophosphate composite material, the sodium iron phosphate pyrophosphate precursor solution in step (1) is prepared as follows: an iron source, a sodium source, a phosphoric acid source, and a solvent are mixed and uniformly mixed to obtain a sodium iron phosphate pyrophosphate precursor solution.

[0019] Furthermore, in the preparation method of the above-mentioned porous carbon-sodium iron phosphate pyrophosphate composite material, the phosphate source includes one or more of phosphoric acid, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, ferrous phosphate, ammonium phosphate, diammonium hydrogen phosphate, sodium ammonium hydrogen phosphate, and diammonium phosphate, preferably phosphoric acid.

[0020] Furthermore, in the preparation method of the above-mentioned porous carbon-sodium iron phosphate pyrophosphate composite material, the iron source is an inorganic iron salt and / or an organic iron salt. More specifically, the iron source can be selected from one or more of ferric chloride, ferric nitrate, ferric sulfate, ferric oxalate, ferric acetate, ferrous oxalate, ammonium ferrous sulfate, and ferric pyrophosphate, preferably ferric chloride.

[0021] Furthermore, in the preparation method of the above-mentioned porous carbon-sodium iron phosphate pyrophosphate composite material, the sodium source is one or more of sodium chloride, sodium nitrate, sodium nitrite, sodium sulfate, sodium hydroxide, sodium bromide, sodium ethoxide, sodium methoxide, sodium acetate, sodium formate, sodium oxalate, sodium oleate, sodium pyrosulfate, sodium pyrophosphate, and sodium bicarbonate, preferably one or more of sodium chloride, sodium nitrate, and sodium acetate.

[0022] Furthermore, in the preparation method of the porous carbon-sodium iron phosphate pyrophosphate composite material, the solvent is at least one of water and an organic solvent. More specifically, the organic solvent can be one or more of ethanol, acetone, methanol, ethylene glycol, n-propanol, and isopropanol.

[0023] Furthermore, in the preparation method of the above-mentioned porous carbon-sodium iron phosphate pyrophosphate composite material, based on the molar ratio, the dosage ratio of the iron source, sodium source and phosphate source can be determined according to the molecular composition of sodium iron phosphate pyrophosphate, wherein the chemical formula of sodium iron phosphate pyrophosphate is Na4Fe3(PO4)2P2O7.

[0024] Furthermore, in the preparation method of the porous carbon-sodium iron phosphate pyrophosphate composite material, the porous carbon is in powder form, and the particle size of the porous carbon is generally 1 to 100 μm, preferably 3 to 20 μm. The pore size distribution of the porous carbon has the following characteristics: the pore volume occupied by the mesopores is 20% to 50% of the total pore volume of the micropores and mesopores, and more preferably 30% to 40%; wherein the pore size of the mesopores is 2 to 50 nm, and the pore size of the micropores is less than 2 nm. The specific surface area of ​​the porous carbon is 500 to 3500 m 2 / g, preferably 1000 to 3000 m 2 / g.

[0025] Furthermore, in the preparation method of the above-mentioned porous carbon-sodium iron phosphate pyrophosphate composite material, the mixing is carried out by impregnation, specifically, the sodium iron phosphate pyrophosphate precursor solution is impregnated with the powdered porous carbon in multiple times, and the sodium iron phosphate pyrophosphate precursor solution is absorbed by the pores of the porous carbon, and the mass ratio of the porous carbon to the sodium iron phosphate pyrophosphate precursor solution is 1:4 to 4:1.

[0026] Furthermore, in the preparation method of the porous carbon-sodium iron phosphate pyrophosphate composite material, the drying conditions in step (2) are: the drying temperature is 60 to 150°C, preferably 80 to 120°C; the drying time is 1 to 24 hours, preferably 2 to 12 hours.

[0027] Furthermore, in the preparation method of the above-mentioned porous carbon-sodium iron phosphate pyrophosphate composite material, the calcination in step (3) is carried out under inert atmosphere and reducing atmosphere conditions, the reducing atmosphere is a mixed gas of hydrogen and inert atmosphere, and the volume content of hydrogen in the mixed gas is 1 to 50%; the inert atmosphere is nitrogen and / or inert gas, and the inert gas is at least one of helium, argon, and neon.

[0028] Furthermore, in the preparation method of the porous carbon-sodium iron phosphate pyrophosphate composite material, the calcination conditions in step (3) are: the calcination temperature is 300-1000°C, preferably 500-800°C; the calcination time is 0.5-8 hours, preferably 1-4 hours.

[0029] Furthermore, in the preparation method of the above-mentioned porous carbon-sodium iron phosphate pyrophosphate composite material, a step (2.1) is also included between step (2) and step (3), and the specific process of the step (2.1) is as follows: in the presence of an alkaline atmosphere, the precursor stream obtained in step (2) is treated, and the stream obtained after the treatment is further dried and calcined to obtain a composite material; the alkaline atmosphere can be at least one of ammonia, ammonium carbonate, ammonium bicarbonate, and ethylenediamine; preferably ammonia; the treatment temperature is 50 to 160°C, preferably 60 to 120°C.

[0030] The third aspect of the present invention provides a porous carbon-sodium iron phosphate pyrophosphate composite material obtained by the above preparation method.

[0031] A fourth aspect of the present invention provides an application of the porous carbon-sodium iron phosphate pyrophosphate composite material or the porous carbon-sodium iron phosphate pyrophosphate composite material obtained by the above preparation method in sodium ion batteries and sodium ion capacitors.

[0032] Compared with the prior art, the porous carbon-sodium iron phosphate pyrophosphate composite material and the preparation method thereof provided by the present invention have the following advantages:

[0033] 1. Sodium iron phosphate pyrophosphate is synthesized by in-situ hydrolysis in a conductive carrier (liquid phase dissolution-in-situ hydrolysis-high temperature calcination), which solves the problem of uneven ion distribution and large particle size in the traditional solid phase method, precipitation method and sol-gel method for synthesizing sodium iron phosphate pyrophosphate. Utilizing the capillary action of the porous material, the sodium iron phosphate pyrophosphate solution is absorbed into the porous material, and after in-situ hydrolysis to form a precursor and high-temperature calcination, the high dispersion and nano-size of the sodium iron phosphate pyrophosphate can be achieved. The existing synthesis method can only synthesize particles with a size of about 100 nanometers after high-energy ball milling, and the specific surface area of ​​the carbon introduced by the surface carbon coating to improve the conductivity is not high, and it cannot provide capacity. It is an inactive substance, which leads to a decrease in the mass specific capacity of the composite material. The present invention proposes to introduce sodium ferric phosphate pyrophosphate into the porous carbon pores, and composite sodium ferric phosphate pyrophosphate, a sodium ion battery positive electrode material (whose theoretical specific capacity can reach 120 mAh / g), in the porous carbon positive electrode, thereby effectively improving the specific capacity of the positive electrode of the sodium ion capacitor, and further improving the electronic conductivity of sodium ferric phosphate pyrophosphate by composite carbon and other conductive materials, and improving the problem of slow sodium ion transmission by reducing the particle size of sodium ferric phosphate pyrophosphate. Comprehensively utilizing the double-layer capacitance, good conductivity and carrier effect of porous carbon, and utilizing the high specific capacity of sodium ferric phosphate pyrophosphate, the two materials can achieve a common optimization effect.

[0034] 2. The porous carbon-sodium iron phosphate pyrophosphate composite material provided by the present invention can improve the tap density of the material and the volume energy density of the device. While the sodium ion battery positive electrode material fills the large-sized pores, most of the micropores are retained, so that the porous carbon of the double-layer capacitor and the sodium ion embedded battery material can work together in the sodium ion capacitor. The two are equivalent to parallel connection, which complement each other in terms of power and energy, and smooth the impact of power load fluctuations on energy storage devices. Compared with the use of sodium ion battery positive electrode materials alone, the method of the present invention can improve the conductivity of sodium ion battery positive electrode materials and reduce safety issues caused by resistive heating.

[0035] 3. In the preparation method of the porous carbon-sodium iron phosphate pyrophosphate composite material provided by the present invention, by introducing the sodium iron phosphate pyrophosphate precursor into the pores of the porous carbon, the grain size of the positive electrode material of the sodium battery can be reduced through the confinement effect of the porous carbon pores, thereby effectively improving the rate performance of the positive electrode material, and reducing the impact on the power density of the sodium ion capacitor while increasing the energy density.

[0036] 4. In the preparation method of the porous carbon-sodium iron phosphate pyrophosphate composite material provided by the present invention, the rate performance of the material can be improved by pretreating the porous carbon powder impregnated with the sodium iron phosphate pyrophosphate solution in an alkaline atmosphere. Pretreatment in an alkaline environment can convert the precursor solution into a precursor in situ, and improve the dispersion of the sodium iron phosphate pyrophosphate particles. The particle size is reduced, so that the solid phase diffusion path of sodium ions in the sodium iron phosphate pyrophosphate particles is reduced, and the sodium iron phosphate pyrophosphate particles are attached in situ to the porous carbon surface to solve its low conductivity problem. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is an XRD comparison diagram of the samples obtained in Example 1 (porous carbon loaded with sodium ferric phosphate pyrophosphate) of the present invention and Comparative Example 1 (acetylene black loaded with sodium ferric phosphate pyrophosphate).

[0038] Figure 2 It is a constant current charge and discharge curve diagram of the pure porous carbon sample before loading in Example 1 of the present invention and the porous carbon loaded sodium iron pyrophosphate sample obtained in Example 1.

[0039] Figure 3 1 is a cyclic voltammogram of the pure porous carbon sample before loading in Example 1 of the present invention and the porous carbon loaded sodium iron phosphate pyrophosphate sample obtained in Example 1. DETAILED DESCRIPTION

[0040] The technical content and effects of the present invention are further illustrated below in conjunction with embodiments, but the present invention is not limited thereby.

[0041] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings and specific embodiments. However, it should be pointed out that the protection scope of the present invention is not limited by these specific implementation modes, but is determined by the claims.

[0042] In the context of this specification, pore volume, specific surface area and pore size distribution are measured using a low temperature nitrogen adsorption method.

[0043] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight.

[0044] In the context of this specification, any two or more embodiments of the present invention may be arbitrarily combined, and the technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0045] Example 1

[0046] Weigh 82.0g of sodium acetate and dissolve it in 100mL of deionized water. Add 202.5g of ferric chloride hexahydrate and 149.1g of ammonium phosphate. Add deionized water to make the volume to 500mL to prepare a precursor solution. Weigh 200g of petroleum coke-based porous carbon powder (specific surface area 3352m 2 / g, pore volume 1.43cm 3 / g, mesoporous volume ratio of 35%, D50 particle size 10μm), put it in an oven and dry it at 100℃ for 5 hours. Add 500mL of precursor solution dropwise to the porous carbon powder, mix the two evenly, and dry the mixture in an oven at 100℃ for 5 hours. Put the mixture in a tube furnace and calcine it at 600℃ for 2 hours under argon atmosphere. The product is marked as AC / NFP-1, and the XRD pattern of the sample is shown in Figure 1 .

[0047] Combination Figure 1 According to the Scherrer formula (D = 0.89λ / (B cosθ), D is the grain size (nm), B is the half-height width of the diffraction peak, θ is the Bragg angle, λ is the wavelength of the X-ray used The crystallinity of the sodium iron pyrophosphate in Example 1 is 12 nm (calculated based on the main diffraction peak of 2-theta=33.1°), which is lower than 22 nm of the sample in Comparative Example 1, which is beneficial to the rate performance of the sodium iron pyrophosphate.

[0048] pass Figure 2 It can be seen that the reversible specific capacity of the pure porous carbon sample before loading is 79.8 mAh / g, and the reversible specific capacity of the porous carbon loaded sodium iron pyrophosphate sample is 98.3 mAh / g, and the specific capacity of loaded sodium iron pyrophosphate is increased by 22%.

[0049] pass Figure 3 It can be seen that the pure porous carbon sample before loading presents a rectangular curve, and the porous carbon loaded sodium iron phosphate pyrophosphate sample shows a series of peaks between 2.7 and 3.3 V, corresponding to the redox peaks caused by the insertion and extraction of sodium iron phosphate, indicating that the increase in the reversible specific capacity of the sample in Example 1 comes from the loading of sodium iron phosphate pyrophosphate.

[0050] Example 2

[0051] Weigh 82.0g of sodium acetate and dissolve it in 100mL of deionized water. Add 107.9g of ferrous oxalate and 115.3g of 85wt% phosphoric acid. Add deionized water to make the volume to 500mL to prepare a precursor solution. Weigh 200g of petroleum coke-based porous carbon powder (specific surface area 3352m 2 / g, pore volume 1.43cm 3 / g, mesoporous volume ratio is 35%, D50 particle size is 10μm), put it in an oven and dry it at 100℃ for 5 hours. Add 500mL of precursor solution dropwise to the porous carbon powder and mix the two evenly. Take 500mL of 25wt% concentrated ammonia water and put it in beaker A, put the mixture in beaker B, put the two beakers in a sealed plastic bucket, put the plastic bucket in a 100℃ blast oven for 12 hours, take out beaker B, put it in a 100℃ blast oven for 6 hours, and then put it in a tubular furnace and calcine it at 600℃ for 2 hours under an argon atmosphere. The product is marked as AC / NFP-N-1.

[0052] Example 3

[0053] Weigh 120g of sodium dihydrogen phosphate, dissolve it in 200mL of deionized water, add 130.4g of ferrous acetate, add 115.3g of 85wt% phosphoric acid, stir, and dilute to 500mL with deionized water to prepare a precursor solution. Weigh 200g of biomass-based porous carbon powder (specific surface area 2251m 2 / g, pore volume 1.12cm 3 / g, mesoporous volume ratio of 25%, D50 particle size 6μm), put it in an oven and dry it at 100℃ for 5 hours. 500mL of the precursor solution was added dropwise to the porous carbon powder, the two were evenly mixed, and put it in a tube furnace and calcined at 500℃ for 4 hours under argon atmosphere. The product is marked as AC / NFP-3.

[0054] Example 4

[0055] Weigh 58.4g of sodium chloride and dissolve it in 100mL of deionized water. Add 303g of ferric nitrate nonahydrate and 115.3g of 85wt% phosphoric acid. Add deionized water to make the volume to 500mL to prepare a precursor solution. Weigh 200g of petroleum coke-based porous carbon powder (specific surface area 3352m 2 / g, pore volume 1.43cm 3 / g, mesoporous volume ratio is 35%, D50 particle size is 10μm), put it in an oven and dry it at 100℃ for 5 hours. Add 500mL of precursor solution dropwise to the porous carbon powder, mix the two evenly, and dry the mixture in a 100℃ oven for 5 hours. Take 300g of ammonium bicarbonate powder and put it in beaker A, put the mixture in beaker B, put the two beakers in a sealed plastic bucket, put the plastic bucket in a 100℃ blast oven for 12 hours, take out beaker B, and after 6 hours in a 100℃ blast oven, put the mixture in a tubular furnace and calcine it at 400℃ for 2 hours in an atmosphere of 90% argon / 10% hydrogen by volume. The product is marked as AC / NFP-N-1-H.

[0056] Example 5

[0057] Weigh 136.1 g of sodium acetate trihydrate, dissolve it in 100 mL of deionized water, add 202.5 g of ferric chloride hexahydrate, add 115.1 g of ammonium dihydrogen phosphate, and dilute to 500 mL with deionized water to prepare a precursor solution. Weigh 200 g of petroleum coke-based porous carbon powder (specific surface area 3352 m 2 / g, pore volume 1.43cm 3 / g, mesoporous volume ratio is 35%, D50 particle size is 10μm), put it in an oven and dry it at 100℃ for 5 hours. Add 500mL of precursor solution dropwise to the porous carbon powder and mix the two evenly. Take 500mL of 25% concentrated ammonia water and put it in beaker A, put the mixture in beaker B, put the two beakers in a sealed plastic bucket, put the plastic bucket in a 100℃ blast oven for 12 hours, take out beaker B, put it in a 100℃ blast oven for 6 hours, and then put it in a tubular furnace and calcine it at 600℃ for 2 hours under an argon atmosphere. The product is marked as AC / NFP-N-2.

[0058] Example 6

[0059] Weigh 136.1 g of sodium acetate trihydrate and dissolve it in a mixed solution of 100 mL of deionized water and 100 mL of ethanol, add 150.0 g of ferric sulfate and 115.3 g of 85% phosphoric acid, and finally dilute to 500 mL with deionized water to prepare a precursor solution. Weigh 150 g of petroleum coke-based porous carbon powder (specific surface area 3352 m 2 / g, the mesopore volume accounts for 35%, and the pore volume is 1.43cm 3 / g, D50 particle size 10μm), put it in an oven and dry it at 100℃ for 5 hours. 500mL of the precursor solution was added dropwise to the porous carbon powder, the two were evenly mixed, and the mixture was dried in an oven at 100℃ for 5 hours. The mixture was placed in a tube furnace and calcined at 700℃ for 2 hours under an argon atmosphere. The product is marked as AC / NFP-4.

[0060] Example 7

[0061] Weigh 85g of sodium nitrate and dissolve it in a mixed solution of 100mL of deionized water and 100mL of ethanol, add 303g of ferric nitrate nonahydrate and 115.3g of ammonium dihydrogen phosphate, and finally dilute to 500mL with deionized water to prepare a precursor solution. Weigh 300g of biomass-based porous carbon powder (specific surface area 2531m 2 / g, pore volume 0.95cm 3 / g, mesoporous volume ratio of 35%, D50 particle size 10μm), put it in an oven and dry it at 100℃ for 5 hours. 500mL of the precursor solution was added dropwise to the porous carbon powder, the two were evenly mixed, and the mixture was dried in an oven at 100℃ for 5 hours. The mixture was placed in a tube furnace and calcined at 600℃ for 2 hours under an argon atmosphere. The product is marked as AC / NFP-5.

[0062] Comparative Example 1

[0063] Weigh 58.4g of sodium chloride, dissolve it in 100mL of deionized water, add 202.5g of ferric chloride hexahydrate, add 115.3g of 85% phosphoric acid, and dilute to 500mL with deionized water to prepare a precursor solution. Weigh 200g of acetylene black powder (specific surface area 10m 2 / g), put it in an oven and dry it at 100°C for 5 hours. Add 500mL of the precursor solution dropwise to acetylene black powder, mix the two evenly, and dry the mixture in an oven at 100°C for 5 hours. Put the mixture in a tube furnace and calcine it at 600°C for 2 hours under an argon atmosphere. The product is marked as C / NFP-1, and the XRD pattern of the sample is shown in Figure 1 .

[0064] Comparative Example 2

[0065] Weigh 82.0g of sodium acetate and dissolve it in 100mL of deionized water. Add 107.9g of ferrous oxalate and 115.3g of 85wt% phosphoric acid. Add deionized water to make the volume to 500mL to prepare a precursor solution. Weigh 200g of acetylene black powder (specific surface area 10m 2 / g), put it in an oven and dry it at 100°C for 5 hours. Add 500mL of the precursor solution dropwise into the porous carbon powder and mix the two evenly. Take 500mL of 25% concentrated ammonia water and put it in beaker A, put the mixture in beaker B, put the two beakers in a sealed plastic bucket, put the plastic bucket in a 100°C forced air oven for 12 hours, take out beaker B, put it in a 100°C forced air oven for 6 hours, and then put it in a tube furnace and calcine it at 600°C for 2 hours under an argon atmosphere. The product is marked as C / NFP-N-1.

[0066] Comparative Example 3

[0067] 134 g of sodium oxalate, 113.1 g of iron phosphate, 28.8 g of ammonium dihydrogen phosphate and 28 g of sucrose were weighed and mixed, ball-milled at 500 rpm for 12 hours, and then placed in a tube furnace and calcined at 350 °C for 5 hours and 800 °C for 2 hours under an argon atmosphere. The product was mixed with 200 g of biomass-based porous carbon powder (specific surface area 2531 m 2 / g, pore volume 0.95cm 3 / g, mesopore volume proportion of 5%, D50 particle size of 10μm) were mixed, and the product was marked as AC-NFP-1.

[0068] Comparative Example 4

[0069] 134 g of sodium oxalate, 113.1 g of iron phosphate, 28.8 g of ammonium dihydrogen phosphate and 28 g of sucrose were weighed and mixed, and ball milled at 500 rpm for 12 h. The product was mixed with 200 g of biomass-based porous carbon powder (specific surface area 3352 m 2 / g, pore volume 1.43cm 3 / g, mesoporous volume ratio of 35%, D50 particle size of 10μm) were mixed, 500mL of 25wt% concentrated ammonia water was placed in beaker A, the mixture was placed in beaker B, the two beakers were placed in a sealed plastic bucket, the plastic bucket was placed in a 100℃ forced air oven and then taken out after 12 hours. The mixture was placed in a tube furnace and calcined at 350℃ for 5 hours and 700℃ for 2 hours under an argon atmosphere. Beaker B was taken out and the product was marked as AC-NFP-1.

[0070] Evaluation test:

[0071] Electrochemical test method: Mix the product, acetylene black (conductive agent) and polyvinylidene fluoride (binder) in N-methylpyrrolidone at a mass ratio of 8:1:1 to prepare a slurry, stir thoroughly and apply it on aluminum foil, and cut the aluminum foil into 12mm discs. Put the cut discs in the positive electrode shell of the button battery, with the side loaded with the product facing up, and add a polypropylene diaphragm with a diameter of 19mm and a metal sodium disc with a diameter of 15.6mm on the discs in turn, and then put the gasket and spring of the button battery respectively, cover the negative electrode shell and package it into a button battery. The reversible specific capacity of the button battery at current densities of 0.1A / g and 2A / g was tested on the Xinwei battery charge and discharge tester, and the cyclic voltammetry curve was tested on the Swiss Metrohm electrochemical workstation.

[0072] Table 1. Reversible specific capacity of samples at different current densities

[0073] sample 0.1A / g (mAh / g) 2A / g (mAh / g) Example 1 98.3 57.4 Example 2 97.5 68.1 Example 3 85.2 45.0 Example 4 99.0 62.3 Example 5 97.2 63.5 Example 6 103.3 55.8 Example 7 87.4 53.0 Comparative Example 1 30.4 10.1 Comparative Example 2 54.1 13.2 Comparative Example 3 65.8 30.6 Comparative Example 4 71.7 35.6

Claims

1. A porous carbon-sodium iron pyrophosphate composite material, the composite material comprising porous carbon and sodium iron pyrophosphate, wherein: Sodium iron phosphate pyrophosphate is distributed on the outer surface of the porous carbon and in the porous carbon channels; based on the total weight of the composite material, the content of the porous carbon is 10wt% to 90wt%, preferably 25wt% to 80wt%.

2. The porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 1, wherein: The specific surface area of ​​porous carbon-sodium iron pyrophosphate composite material is 1000~3600m 2 / g, preferably 2500 to 3400 m 2 / g.

3. The porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 1, wherein: The pore size distribution of the composite material has the following characteristics: the pore volume occupied by the mesopores is 5% to 50% of the total pore volume of the micropores and the mesopores, and more preferably 10% to 30%.

4. The porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 1, wherein: The particle size of the porous carbon is 1-100 μm, preferably 3-20 μm; the pore size distribution of the porous carbon has the following characteristics: the pore volume occupied by the mesopores is 20%-50% of the total pore volume of micropores and mesopores, preferably 30%-40%.

5. The porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 1, wherein: In the porous carbon-sodium iron phosphate pyrophosphate composite material, the crystal size of the sodium iron phosphate pyrophosphate is 2 to 50 nm, preferably 5 to 20 nm.

6. A method for preparing a porous carbon-sodium iron phosphate pyrophosphate composite material, the preparation method comprising the following steps: (1) preparing a sodium iron phosphate pyrophosphate precursor solution, mixing an iron source, a sodium source, a phosphoric acid source, and a solvent, and mixing them evenly to obtain a sodium iron phosphate pyrophosphate precursor solution; (2) mixing the sodium iron phosphate pyrophosphate precursor solution obtained in step (1) with porous carbon to obtain a precursor stream after mixing; (3) The precursor material obtained in step (2) is dried and calcined to obtain a porous carbon-sodium iron pyrophosphate composite material.

7. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 6, wherein: The phosphoric acid source includes one or more of phosphoric acid, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, ferrous phosphate, ammonium phosphate, diammonium hydrogen phosphate, sodium ammonium hydrogen phosphate, and ammonium dihydrogen phosphate, preferably phosphoric acid.

8. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 6, wherein: The iron source is an inorganic iron salt and / or an organic iron salt, and the iron source is selected from one or more of ferric chloride, ferric nitrate, ferric sulfate, ferric oxalate, ferric acetate, ferrous oxalate, ammonium ferrous sulfate, and ferric pyrophosphate, preferably ferric chloride.

9. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 6, wherein: The sodium source is one or more of sodium chloride, sodium nitrate, sodium nitrite, sodium sulfate, sodium hydroxide, sodium bromide, sodium ethoxide, sodium methoxide, sodium acetate, sodium formate, sodium oxalate, sodium oleate, sodium pyrosulfate, sodium pyrophosphate, and sodium bicarbonate, preferably one or more of sodium chloride, sodium nitrate, and sodium acetate.

10. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 6, wherein: The pore size distribution of porous carbon has the following characteristics: the pore volume occupied by mesopores is 20% to 50% of the total pore volume of micropores and mesopores, and more preferably 30% to 40%; the specific surface area of ​​porous carbon is 500 to 3500 m 2 / g, preferably 1000 to 3000 m 2 / g.

11. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 6, wherein: The solvent is at least one of water and an organic solvent, and the organic solvent is one or more of ethanol, acetone, methanol, ethylene glycol, n-propanol, and isopropanol.

12. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 6, wherein: The mass ratio of porous carbon to sodium iron pyrophosphate precursor solution is 1:4 to 4:

1.

13. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 6, wherein: The drying conditions in step (2) are as follows: the drying temperature is 60 to 150° C., preferably 80 to 120° C.; the drying time is 1 to 24 hours, preferably 2 to 12 hours.

14. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 6, wherein: The calcination in step (3) is carried out under an inert atmosphere or a reducing atmosphere. The reducing atmosphere is a mixed gas of hydrogen and an inert atmosphere, wherein the volume content of hydrogen in the mixed gas is 1 to 50%; the inert atmosphere is nitrogen and / or an inert gas, wherein the inert gas is at least one of helium, argon and neon.

15. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 6, wherein: The calcination conditions in step (3) are as follows: the calcination temperature is 300 to 1000° C., preferably 500 to 800° C.; the calcination time is 0.5 to 8 hours, preferably 1 to 4 hours.

16. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 6, wherein: Between step (2) and step (3) there is also a step (2.1), and the process of step (2.1) is as follows: in the presence of an alkaline atmosphere, the precursor stream obtained in step (2) is treated, and the stream obtained after the treatment is dried and calcined to obtain a composite material.

17. The method for preparing the porous carbon-sodium iron phosphate pyrophosphate composite material according to claim 16, wherein: The alkaline atmosphere is at least one of ammonia, ammonium carbonate, ammonium bicarbonate, and ethylenediamine, preferably ammonia; the treatment temperature is 50 to 160°C, preferably 60 to 120°C.

18. Use of the porous carbon-sodium iron phosphate pyrophosphate composite material according to any one of claims 1 to 5, or the porous carbon-sodium iron phosphate pyrophosphate composite material obtained by the preparation method according to any one of claims 6 to 17 in sodium ion batteries and sodium ion capacitors.

Citation Information

Cited By

  • Composite polyanionic sodium battery positive electrode material as well as preparation method and application thereof

    CN120664514A